Knowledge and Readiness of Nurses in Carrying Out Restrain and Seclusion - Malfasari, Eka; Devita, Yeni; Adelia, Gita (Global Health Science Group, 2024)
Mental health is a significant issue worldwide, including in Indonesia. Over 1 billion people worldwide experience mental disorders, and the prevalence of mental disorders in Indonesia aligns with global data. Mental disorders can lead to a decrease in quality of life and hinder daily activities. Severe or chronic mental disorders tend to result in aggressive behavior and can pose a threat to the safety of oneself and others. Restraint and seclusion measures are often used to reduce violence in patients with mental disorders, despite their negative impact on patients and nurses. Increasing nurses' knowledge and readiness in implementing restraint and seclusion can reduce the risk of negative outcomes and accidents. This study aims to assess nurses' knowledge and readiness in controlling patients in a psychiatric hospital. This is a quantitative study with a descriptive research design conducted at Tampan Psychiatric Hospital in Pekanbaru, Riau Province. The sample size for this study was 94 nurses, selected using total sampling technique. The knowledge instrument in this study consisted of 11 items, measured using the Gutman scale, while the readiness instrument consisted of 46 items, measured using the Likert scale. The results of this study revealed that the majority of nurses were in the age range of >35 years (60.4%). In terms of gender, the majority of nurses were female (59.6%), and most nurses had a Bachelor's degree (59.6%). In terms of position, the majority of nurses held honorary positions (52.1%). Furthermore, the majority of nurses had a high level of knowledge in implementing restraint and seclusion, with a total of 54 (57.45%) individuals. However, most nurses had poor readiness in implementing restraint and seclusion, with a total of 57 (60.44%) individuals.